Communications and Computer Security - Ince, A. Nejat; Wilhelmsen, Dag; Sankur, Bülent (Springer US, 1995)
WIS is being planned and developed to meet the communications requirements of the Authority. WIS will be a digital network, largely following CCITT, IDN/ISDN standards and recommendations. The study of the WIS COMSEC/COMPUSEC subsystem, as developed and presented in this chapter was carried out in the light of the requirements summarized in Chapter 2.